TAX RULES AND INDUCTIVE RULES: AN ANALYSIS OF TAX REPLACEMENT AND INTERVENTION IN FREE COMPETITION (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2023)
The State has several ways of intervening in the economic order, which can be directly, indirectly or through inducing norms. When we talk about inducing norms, we must first observe their purpose at the time of elaboration, as it will be their justification for continuing to integrate the Brazilian legal system. Tax-inducing rules are always used to intervene in the economic order, which received several constitutional protections after the 1988 edition of the Federal Constitution. Keywords: Economic order; Free competition; Contribution capacity; Inducing norms; “Forward” tax substitution